Peak-Inspiratory-Flow-Rate Guided Inhalation Therapy Reduce Severe Exacerbation of COPD - Chen, Shih-Yu; Huang, Chun-Kai; Peng, Hui-Chuan; Tsai, Hsing-Chen; Huang, Szu-Ying; Yu, Chong-Jen; Chien, Jung-Yien (Frontiers in Pharmacology, 2021)
Optimal peak inspiratory flow rate (PIFR) is crucial for inhalation therapy in patients with chronic obstructive pulmonary disease (COPD). However, little is known about the impact of PIFR-guided inhalation therapy on the clinical outcomes among patients with varying severities of COPD. A PIFR-guided inhalation therapy, including PIFR assessment and PIFR-guided inhaler education, was introduced in a pay-for-performance COPD management program in National Taiwan University Hospital. Among 383 COPD patients, there was significant reduction in incidence of severe acute exacerbation in the PIFR-guided inhalation therapy (PIFR group) than conventional inhaler education (control group) (11.9% vs. 21.1%, p=0.019) during one-year follow-up. A multivariable Cox’s proportional-hazards analysis revealed that the PIFR-guided inhalation therapy was a significant, independent factor associated with the reduced risk of severe exacerbation (adjusted hazard ratio=0.49, 95% confidence interval, 0.28-0.84, p=0.011). Subgroup analysis found PIFR-guided inhalation therapy was more beneficial to patients with older age, short body stature, COPD stage 1&2, group C&D (frequent exacerbation phenotype), and using multiple inhalers. This study showed the PIFR-guided inhalation therapy significantly reduced the incidence of severe acute exacerbation than conventional inhaler education in patients with COPD. Careful PIFR-assessment and education would be crucial in the management of COPD.